A Retrospective Study: Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis - Yuli Wahyu Rahmawati; Diah Mira Indramaya (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) is rare, but threaten the patient's life. Purpose: To evaluate management of SJS and TEN. Methods: A  retrospective study to patient with SJS and TEN in  2011-2014, data regarding the prevalent of patients, history of patients, etiology, clinical manifestation, supporting of examination, therapy, complication, mortality, follow up, and duration of treatment patients recorded from medical report. Result: Total patient with SSJ and NET were 37 patients. Most patients were female (73%) with majority age range 25-44 years (48.6%), epilepsy is the most comorbidities (27%), the main etiology the use of drug (62.1%), the highest class of drugs is analgesic drugs (38.6%), 37 patients using corticosteroid for therapy (100%), skin is the most complication (50.9%), and death rate was zero (0%). Conclusion: Management of patients with SJS and TEN gives complete recovery. Key words: Stevens-Johnson syndrome, toxic epidermal necrolysis, management.